Pengaruh Penggunaan Metode Diskusi Kelompok dan Metode Ceramah Terhadap Hasil Belajar Pendidikan Kewarganegaraan Siswa Kelas VII MTs Miftahul Mubtadiin - Rifi Hamdani; Sunardjo; Dian Eka Indriani (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
Civics Education (PKn) is a subject that aims to educate students to foster morale and to make good citizens, which is expected to be realized in daily life, both within the school environment and outside the school environment. Civics education (PKn) was originally supposed to be able to shape the activeness, creativity, and intelligent thinking of students in solving any existing problem by way of consensus agreement in accordance with the IV points of Pancasila precepts, namely "Democracy led by wisdom in consultation and representation". Civics is a lesson about government and civic obligations relating to the state or between citizens'. This research uses a quantitative research type of quasi-experiment by using one variable to know the learning achievement, namely, affective, cognitive and psychomotor, which aims to determine the effect and differences in group discussion methods and lecture methods on results. Based on the data analysis, it can be concluded that shows that civics education (PKn) learning with group discussion method is better than lecture learning. There are differences in student learning achievement after using the group discussion method in the subjects of Civics Class VII A/ B MTs Miftahul Mubtadiin.